A worst-case scenario based methodology to assess the environmental impact of land use planning. (September 2017) - Chen, Longgao; Li, Long; Yang, Xiaoyan; Zheng, Jian; Chen, Longqian; Shen, Zhengping; Kervyn, Matthieu
Abstract: The implementation of inappropriate land use planning has negative impact on environmental quality, threatens food, health and residential security, and can even lead to regional environmental disaster. In this paper, a worst-case scenario based methodology using the land use environmental tolerance index (LETI) was proposed to assess the impact of land use planning on the environment. The land use planning environmental impact assessment (LUPEA) of Lianyungang City was performed as a case study to demonstrate the novel methodology. The inappropriate land use planning of the study area was spatially identified, and adjustments for the land use planning scheme to minimize the adverse impacts were accordingly recommended. Results show that the land use planning layout of the study area is fundamentally rational as most of the planned production and living land parcels are located outside the worst-case scenario areas, but the small fraction of the parcels in the worst-case scenario areas indicates a need for an improved land use planning scheme. This methodology provides a new perspective to evaluate the impact of land use planning on the environment, especially for densely populated countries which still suffer food, health and residential security issues and thus require much attention to environmental safety. Highlights: The worst-case scenario is introduced to assess land use planning environmental impact. It includes land use environmental tolerance index in the assessment. It is helpful for developing countries to address environmental problems.